2016
DOI: 10.1002/mnfr.201500820
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of tomato polyphenols is enhanced by processing and fat addition: Evidence from a randomized feeding trial

Abstract: Flavanones and flavonols in ROOE presented higher bioavailability, suggesting that the processing undergone by the raw tomato improved their absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 36 publications
(62 reference statements)
1
55
0
1
Order By: Relevance
“…(e)). Martínez‐Huélamo et al . reported that, compared with raw tomatoes, the FAH content of tomato sauces was not affected by processing but decreased when olive oil was added.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…(e)). Martínez‐Huélamo et al . reported that, compared with raw tomatoes, the FAH content of tomato sauces was not affected by processing but decreased when olive oil was added.…”
Section: Resultsmentioning
confidence: 99%
“…In the same study, naringenin levels were higher with 10% of EVOO than 5%, probably because of enhanced solubility, whereas the oil content did not affect the degradation pattern. Martínez-Huélamo et al 20 found that processing increased the naringenin concentrations in tomato sauce, compared to the raw fruit, even more so if oil was used. Tomas et al 6 reported a statistically significant increase of naringenin in home-made versus industrial tomato sauce and fresh fruit.…”
Section: Effect Of the Sofrito Technique On Naringeninmentioning
confidence: 99%
See 2 more Smart Citations
“…In a clinical study of healthy people, Mart ınez et al found that processing tomatoes into sauces improve the bioavailability of flavanones, flavanols, and some hydroxycinnamic acids, as reflected by the increase in the area under the plasma concentration versus time curve (Martinez-Huelamo et al 2016). It has likewise been observed that their plasma half-life was increased, especially after ingesting refined olive oil, indicating that the processing experienced by raw tomatoes improves their absorption.…”
Section: The Limitations Of Dietary Flavonoids In Clinical Applicationmentioning
confidence: 99%